Lost worlds of ancient and modern Greece : Gilbert Bagnani : the adventures of a young Italian archaeologist in Greece, 1921-1924 - Begg, D. J. Ian, (Archaeopress archaeological lives., 2020)
This volume relates three years (1921-1924) in the life of Gilbert Bagnani, a young Italian archaeologist in Greece, based on his letters to his mother in Rome, at first as a non-partisan observer of, and later as an active participant in, some of the most tumultuous events in modern Greek history.